Kidnapped at Sea: Kidnapped at Sea: The Civil War Journey of David Henry White - Hirsch, Alan (New Agenda: SA Journal of Social and Economic Policy, 2025)
Kidnapped at Sea tells the true story of a free black teenager, David Henry White from Delaware on the east coast of the United States, who was captured from a transatlantic merchant vessel where he served as a junior member of the kitchen staff and held as a slave on the rebel warship Alabama. Captained by slave-owner and committed rebel Raphael Semmes, Alabama roamed the north and south Atlantic and the Indian Ocean, capturing, burning or ransoming dozens of US merchant ships, fighting off one US warship and finally being sunk in battle by another. White, who could not swim, was abandoned and drowned. nThe arc of the story sweeps from Civil War US, following Alabama from its shipyard in the UK to the US, and then back across the north Atlantic, down to Brazil, to Saldanha Bay, Cape Town and Simonstown, across to south east Asia, back to the south Atlantic, to temporary respite in a French port and its demise in international waters between France and the UK. The story demonstrates how the conflict impacted many and implicated some in its global theatre of war.